2004
DOI: 10.1162/089892904970771
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration Sites Identified by Perception of Spatial Wavelet Filtered Visual Speech Gesture Information

Abstract: Perception of speech is improved when presentation of the audio signal is accompanied by concordant visual speech gesture information. This enhancement is most prevalent when the audio signal is degraded. One potential means by which the brain affords perceptual enhancement is thought to be through the integration of concordant information from multiple sensory channels in a common site of convergence, multisensory integration (MSI) sites. Some studies have identified potential sites in the superior temporal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 52 publications
(177 reference statements)
9
81
0
1
Order By: Relevance
“…2004). Similarly, our study controlled for these factors by using the very same audio‐visual inputs in which the only manipulation was blurring of the mouth area, keeping gross movements and onset/offset the same.…”
Section: Discussionmentioning
confidence: 99%
“…2004). Similarly, our study controlled for these factors by using the very same audio‐visual inputs in which the only manipulation was blurring of the mouth area, keeping gross movements and onset/offset the same.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also of relevance for the neural mechanisms involved in multisensory processing of audiovisual speech. Neuroimaging and electrophysiological studies have found audiovisual interactions in multimodal areas such as the superior temporal sulcus (STS) and sensory-specific areas including the auditory and visual cortices (Besle et al, 2004;Callan et al, 2004). It has been proposed that the unimodal inputs are initially integrated in STS and that interactions in the primary auditory and visual cortices reflect feedback from STS (Calvert et al, 1999).…”
Section: -General Discussionmentioning
confidence: 99%
“…Callan et al 2004;Calvert & Lewis 2004;Capek et al 2004;Miller & D'Esposito 2005). Some well-established findings are itemized here, which will then be examined in relation to the 'two-mode' sketch outlined in §5.…”
Section: Neural Mechanisms For Audio-visual and Visual Speechmentioning
confidence: 93%